MODEL PEMBELAJARAN MANDIRI DALAM MENINGKATKAN KOMPETENSI DAN KEMANDIRIAN PESERTA KURSUS: Studi di LKP Pelita Massa Jawa Barat. - Shantini, Yanti (2010)
The data in 2008 illustrated that the total target of courses in West Java is 10.943 persons with the budget provided is 17 billion as the source of subsidy aid fund. This finance is intended to fund many types of courses program. The amount of the provided fund needs to balance good and innovative management in order to attain the goal of producing skillful workers. This research studies how a learning model based on the skill can produce its graduates to have the sewing competion and to gain the level of independence after finishing the program. The effort to generate qualified human resources is attained through the cooperation of many sides of the party who are involved in the program. This is in line with Claslee (1931) mentioning that the involvement of society in the success of the program is required in its role as the education medium for its people. In addition, InWent (2003) elaborates that the implementation of these educational services should adjust the changes in the market structure, the innovation in technology and the new methods in organizing the work. He further adds that these educational services implementation definitely requires new knowledge and development especially in the field of competence. One of the ways in conducting this learning innovation is by having this inventive learning as the development of constructivist paradigm. Yamin (2008). This research employs the procedure of research and development by applying joint method including qualitative and quantative approaches. Qualitative approach is utilized to describe the actual condition of courses program implementation in West Java and the skill learning model of LKP Pelita Massa. Quantitative approach, on the other hand, measures the effectiveness of the model developed using true experiment method with pos-test control design as the technique. First, based on the exploration of institutional studies courses in West Java continues to experience growth and change in accordance with government policy and the needs of the community. Second, The conceptual model developed self directed learning activities designed through the planning, implementation and evaluation, based on the competence developed sewing. Third, implementation of the conceptual model developed can enhance the competence and independence of the course participants to effectively and efficiently. Forth, effectiveness of the learning model was tested in real conditions in the LKP Pelita Massa has shown that the experimental group has the competence and independence of values better than those who were not being subjected to model self directed learning skills. The course of the independent learning with sewing specialty has evidently been able to improve the competence and to encourage students' independence. Hence, it is expected that this program can be one of the inputs in the implementation of subsiding courses conducted by both courses institution and government considering their roles as finance supplier so that the attempt of producing skillful workers in the society can be attained.